Luminescent closed shell nickel(ii) pyridyl-azo-oximates and the open shell anion radical congener: molecular and electronic structure, ligand redox behaviour and biological activity. (4th May 2017) - Pramanik, Shuvam; Dutta, Suhana; Roy, Sima; Dinda, Soumitra; Ghorui, Tapas; Kumar Mitra, Arup; Pramanik, Kausikisankar; Ganguly, Sanjib
Abstract : Luminescent nickel(ii ) complexes have been synthesized using redox-active azo-oximes. The superior π-acidity of the organic backbone is a key to the isolation of Ni(ii ) anion radicals. Abstract : Luminescent nickel(ii ) complexes of type [Ni II (L −I )2 ], 2, have been synthesized using photosensitizer redox-active oxime ligands HL, 1, incorporating the π-acidic azo and pyridyl functions. The redox non-innocent behaviour of the ligands has been exploited to isolate the open shell Ni(ii )-bound azo-oxime anion radical complexes of type Et4 N[Ni II (L −I )2 − ], 3, via reduction with NaBH4 . The superior stabilization of the unpaired spin over the ligand framework has been established by EPR and DFT studies. The anti-bacterial activity of2 has been scrutinized and it has been found to exhibit potential radical scavenging activity.